PERSETERUAN ARAB DAN PERSIA DALAM GERAKAN PEMALSUAN HADIS PADA MASA KEPEMIMPINAN AL-MA’MUN: Istilah Kaum Zindiq dan Perkembangannya di Dunia Islam, Perkembangan Hadis Abad Ke-III Hijriah, Motif Kaum Zindiq Persia dalam Memalsukan Hadis di Abad Ke-III Hijriah Masa Kepemimpinan Al-Makmun. - Zainal Arifin (Jurnal Studi Islam, 2025)
During the 3rd century Hijri, under the leadership of al-Maʾmūn, the Mutakallimūn (Islamic theologians) posed a significant challenge to the ḥadīth scholars. Al-Maʾmūn, who possessed profound knowledge of the Qurʾān, ḥadīth, and Persian and Greek philosophy, initiated discussions among scholars specializing in kalām (Islamic theology), fiqh (Islamic jurisprudence), and ḥadīth. In these discussions, al-Maʾmūn tended to support the views of the theologians, including the notion of the createdness of the Qurʾān, despite the long-standing conflict between the ḥadīth scholars and the theologians. This conflict provided an opportunity for the Zindīq (heretics) to forge ḥadīths, leading to a proliferation of forged ḥadīths during this period. The unique aspect of this forgery by the Zindīq invites an investigation into their motives for fabricating ḥadīths in the 3rd century Hijri during al-Maʾmūn’s reign. This study employs a qualitative research method with a library research approach, utilizing historical social theory. The findings conclude that the Zindīq’s motives for fabricating ḥadīths were not only to undermine or obscure Islamic teachings but also to elevate the status of the Persian nation. Key words: 3rd-century hadis, Zindiq, forged hadis.